O35 B-cell depletion and response in a randomized, controlled trial of obinutuzumab for proliferative lupus nephritis. (23rd March 2020) - Furie, Richard; Cascino, Matthew D; Garg, Jay P; Aroca, Gustavo; Alvarez, Analía; Fragoso-Loyo, Hilda; Santillán, Elizabeth Zuta; Malvar, Ana; Brunetta, Paul G; Schindler, Thomas; Looney, Cary Michael Donna; Hassan, Imran; et al.
Abstract : Background: Previous analyses identified associations between the degree of B-cell depletion and response in lupus nephritis (LN). NOBILITY tested whether enhanced B-cell depletion with the type II anti-CD20 mAb obinutuzumab could improve responses in LN. Methods: 126 patients with active Class III/IV LN were randomized to obinutuzumab or placebo infusions in combination with mycophenolate and corticosteroids. Peripheral B-cells were measured using a flow cytometry method with a lower limit of 0.441 cells/μL. Sustained depletion was assessed by flow cytometry measurements at weeks 24 and 52. Results: Obinutuzumab was associated with increased CRR (40% vs. 18%, P=0.007) and ORR (51% vs. 29%, P =0.015) at week 76. Obinutuzumab resulted in rapid and complete depletion of peripheral B-cells, memory and naïve B-cell subsets, and plasmablasts, with 89% of obinutuzumab patients depleted to <0.441 CD19+ cells/μL at week 4. Among obinutuzumab patients, sustained B-cell depletion was associated with greater renal response at week 76 (table 1 ), although patients who achieved sustained depletion also had lower baseline proteinuria and serum creatinine. Conclusions: Obinutuzumab, a type II anti-CD20 mAb, induced rapid and complete depletion of peripheral B-cells and B-cell subsets. Similar to previous reports, sustained B-cell depletion was associated with increased renal response. Further evaluation is ongoing to understand the factors associated with achievement of sustained B-cell depletion and renal response. Acknowledgements: This study was funded by F. Hoffmann-La Roche.